Cash Waqf Linked Sukuk: A Sharia-Compliant Model for Sustainable Development - Paul, Wina; Faudji , Rachmad (Journal of Economicate Studies, 2021)
This study explores Cash Waqf Linked Sukuk (CWLS) as a Sharia-compliant financial innovation for sustainable Islamic economic development. By integrating the philanthropic principles of waqf with the structured investment potential of sukuk, CWLS serves as a blended model that aligns with maqāṣid al-sharīʿah. The research adopts a qualitative-descriptive approach, reviewing classical Islamic finance theory and modern policy implementations. Findings show that CWLS can finance key sectors such as education, healthcare, and infrastructure without burdening public budgets. It mobilizes dormant charitable capital, enhances financial inclusion, and institutionalizes ethical governance. The study also identifies implementation barriers, including regulatory fragmentation and institutional inefficiencies, and proposes solutions grounded in legal harmonization and capacity building. This research contributes conceptually by framing CWLS as an ethical investment vehicle and practically by offering policy directions for governments and waqf institutions. CWLS is shown to be a viable tool for long-term, inclusive, and spiritually guided development.